No evidence for an mtDNA role in sperm motility: data from complete sequencing of asthenozoospermic males - Pereira, L (2007)
The first complete mitochondrial DNA (mtDNA) sequences (approximately 16,569 bp) in 20 patients with asthenozoospermia and a comparison with 23 new complete mtDNA sequences in teratoasthenozoospermic individuals, confirmed no sharing of specific polymorphisms or specific mitochondrial lineages between these individuals. This is strong evidence against the accepted claim of a major role played by mtDNA in male fertility, once supported by haplogroup association studies based on the screening of hypervariable region I. The hypothesis of maternally driven selection acting in male reproductive success must thus be treated with caution.